2010
DOI: 10.1007/s11191-010-9285-4
|View full text |Cite
|
Sign up to set email alerts
|

Why Implementing History and Philosophy in School Science Education is a Challenge: An Analysis of Obstacles

Abstract: Teaching and learning with history and philosophy of science (HPS) has been, and continues to be, supported by science educators. While science education standards documents in many countries also stress the importance of teaching and learning with HPS, the approach still suffers from ineffective implementation in school science teaching. In order to better understand this problem, an analysis of the obstacles of implementing HPS into classrooms was undertaken. The obstacles taken into account were structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
81

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(162 citation statements)
references
References 73 publications
2
79
0
81
Order By: Relevance
“…Discussions regarding the goals and aims of school science are far from novel, but have been a topic at least since the beginning of the twentieth century (Rudolph 2005). It is also evident that the diverging goals will be connected to very different forms of teaching, where the focus on concepts has been known to follow strict patterns of teacher-centered transmission of knowledge (Bartholomew et al 2004;Höttecke and Silva 2011).…”
Section: Aims and Goals Of School Sciencementioning
confidence: 99%
See 4 more Smart Citations
“…Discussions regarding the goals and aims of school science are far from novel, but have been a topic at least since the beginning of the twentieth century (Rudolph 2005). It is also evident that the diverging goals will be connected to very different forms of teaching, where the focus on concepts has been known to follow strict patterns of teacher-centered transmission of knowledge (Bartholomew et al 2004;Höttecke and Silva 2011).…”
Section: Aims and Goals Of School Sciencementioning
confidence: 99%
“…Most teachers are deeply rooted in a school-science culture that has its starting point within science and uses the structured teaching formats connected to this way of viewing the goals of science education (Roberts 2011). This means that including new elements, both issues and teaching formats, that does not fit with the current teaching culture can be very challenging for teachers (Aikenhead 2006;Bartholomew et al 2004;Höttecke and Silva 2011). In a recent study, Leden et al (2015) reported on perspectives on NOS teaching put forward by teachers who had no previous NOS teaching experience.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 3 more Smart Citations